ОЮУ ЧИХТ ХАН ХӨВГҮҮНИЙ ТУУЖ ОРШИВ ЗОХИОЛЫН ЭХ СУРВАЛЖУУД - А. Мөнхцэцэг (Acta Mongolica, 2014)
From the Buddhist expansion in the 17th century, India, Tibet, and Mongolia became connected through literature as they influenced each other in that regard. One such example is a text known as ‘The legend of Prince Gyü čiketü’ whose main topic, composition, and story line is inspired by Buddhist doctrine of filial piety. A comparative study of this Mongol text reveals similarities with the following Indian and Tibetan texts.1.A Mongol version of the Indian legend about King Vicrāmadya, (Boγda Biγarmijid qaγan-u terigün debter) in its Volume 1, section 14 that reads: ‘The tale of the vampire wife is the 13th chapter of the Mongol collection of tales concerning king Vikramaditya and his throne, Bigarmijid’, translated by and was published in Bawden, C. R. 1960. Tales of King Vikramaditya and the Thirty -two Wooden Men. New Delhi. 155-162, no.13 The text portrays King Vicrāmadya as Gyü čiketü (prince Turquoise-ears) who defeated the devil and inspired by the main topic in literature, the young prince goes to live with his step-mother.